Curriculum development for medical education a six-step approach - Thomas, Patricia A. (Patricia Ann), 1950-; Kern, David E.; Hughes, Mark T.; Tackett, Sean A., 1982-; Chen, Belinda Y., 1966- (Johns Hopkins University Press, 2022)
"This book presents a practical framework for the development, implementation, and dissemination of quality health professions curricula. The book is intended for faculty and others who, while content experts, may not have a background in education or implementation science but have an interest or responsibility as educators in their discipline"--